Bargaining in spectrum auctions: A review of the German auction in 2015. Issue 5 (June 2017) - Bichler, Martin; Gretschko, Vitali; Janssen, Maarten
Abstract: Germany was the first country in Europe that auctioned off spectrum in the valuable 700 MHz band for mobile telecommunication usage. The German regulator decided to sell this spectrum together with spectrum in the 900 MHz and 1800 MHz legacy bands. With only the three incumbent operators bidding in the auction and a relatively transparent auction design, it was possible to get a very clear impression of the actual bidding behaviour. We show that in the beginning of the auction, bidders were actively searching for a way to allocate the available spectrum that all bidders could agree to at low prices. Bidders were teaching each other what they should bid and were providing carrots and sticks. When the excess demand was concentrated in one band only, bidders started to compete head on leading to a war of attrition. This competition only stopped when bidders started to raise prices in bands that were already cleared. We interpret this bidding behaviour in terms of bidders expressing allocative externalities and conclude that the ability to do so may be regarded as a positive aspect of the transparent design.